History, power, ideology : central issues in Marxism and anthropology - Donham, Donald L. (Donald Lewis) (University of California Press, 1999)
Is Marxism a reflection of the conceptual system it fights against, rather than a truly comprehensive approach to human history? This work confronts this problem in analyzing a radically different social order: the former Maale kingdom of southern Ethiopia.